2015
DOI: 10.1063/1.4918402
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of foaming polypropylene modified with ramified polymer

Abstract: Polypropylene foams have great industrial interest because of balanced physical and mechanical properties, recyclability as well as low material cost. During the foaming process, the elongational forces applied to produce the expanded polymer are strong enough to rupture cell walls. As a result, final foam has a high amount of coalesced as well as opened cells which decreases mechanical and also physical properties. To increase melt strength and also avoid the coalescence effect, one of the current solution is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Low solubility and diffusivity of blowing agents in PP have been determined [258,259], leading to inhomogeneous morphology along the part. On the other hand, the [261,262], ramified molecular structures [157,260] and blending with other polymer [125,[263][264][265][266]. Furthermore, it has been reported that inorganic fillers dramatically enhance cell structure of foamed polymers acting as nucleating agents.…”
Section: Chapter 5: Pp 20gf -Mucell® Foamsmentioning
confidence: 99%
“…Low solubility and diffusivity of blowing agents in PP have been determined [258,259], leading to inhomogeneous morphology along the part. On the other hand, the [261,262], ramified molecular structures [157,260] and blending with other polymer [125,[263][264][265][266]. Furthermore, it has been reported that inorganic fillers dramatically enhance cell structure of foamed polymers acting as nucleating agents.…”
Section: Chapter 5: Pp 20gf -Mucell® Foamsmentioning
confidence: 99%
“…Low solubility and diffusivity of blowing agents in PP have been determined [258,259], leading to inhomogeneous morphology along the part. On the other hand, the weak melt strength promotes cell walls breakage under elongational forces while processing, causing cell coalescence and open-cell structures and decreasing mechanical properties [260].…”
Section: Pp 20gf -Mucell® Foamsmentioning
confidence: 99%
“…Different methods have been conducted aimed to improve cell nucleation behavior and melt strength of PP, such as long-chain branching [261,262], ramified molecular structures [157,260] and blending with other polymer [125,[263][264][265][266]. Furthermore, it has been reported that inorganic fillers dramatically enhance cell structure of foamed polymers acting as nucleating agents.…”
Section: Pp 20gf -Mucell® Foamsmentioning
confidence: 99%